The Evaluation of Occupational Safety and Health Based on Employee Behavior Aspect in Production Process at Pabrik Gondorukem and Terpentin Rejowinangun – Trenggalek - Lutfi, Musthofa; Nugroho, Wahyunanto Agung; Prasetyo, Ary Drajad (Jurnal Teknologi Pertanian, 2013)
Occupational health and safety is important to avoid accident in production process. Pabrik Gondorukem and Terpentin (PGT) Rejowinangun is a factory that processes pine latex to produce gondorukem and terpentin that have high levels of workplace accidents. In this study, occupational health and safety evaluation performed by evaluate facility, workroom, working condition, and health and working safety implement at sectioned production process corresponds to behaviour aspect and employ safety default then give remedial recommendation proposal job on work area of that evaluation result. Study result show that amelioration of working location in Pabrik Gondorukem and Terpentin is required to improve occupational health and safety. Dangerous employee behavior such as the employee awareness to wear safety equipment, cleanliness of the area and company safety and health management is need to be improved. Keywords: ergonomic, gondorukem, occupational health and safety